Grain yield and quality of wheat are improved through post-flowering foliar application of zinc and 6- benzylaminopurine under water deficit condition - Zarea, Mohammad Javad; Karimi, Nasrin (Frontiers in Plant Science, 2023)
Zinc (Zn) as an essential micronutrient and cytokinin as phytohormone not only regulate plant growth but also play fundamental roles in plant tolerance against drought stress. Underrating the function and the role of cytokinin in combined with an essential micronutrient, Zn, could improve the choice of a sustainable strategy for improvement of plant drought stress. The weight of grain is the most important component of wheat that determines grain yield. Water stress during the grain-filling period reduces endosperm cell division, resulting in reduction of grain sink potential and subsequently grain mass at maturity. Cytokinins play a vital role in the stimulation of cell division during the early grain-filling stages. Farm field trials were implemented to assess the response of drought-imposed winter wheat to foliar application of 6-benzylaminopurine (6-BAP) and ZnSO4. Winter wheat plants were exposed to water stress at anthesis. Plants were single foliar sprayed with various combinations of Zn levels (0 and 0.6%) and 6-BAP (0, 10, and 20 mg L-1). 6-benzylaminopurine and Zn were foliar applied 2 days before drought imposition. We found that the drought stress significantly decreased 1000-grain that was accompanied with over-expression of cytokinin oxidase/dehydrogenase (TaCKX). Foliar application of Zn increased the concentration of Zn in grains. Applying Zn increased yield, straw dry weight, and kernel weight relative to plants sprayed with water alone. Increased grain yield due to foliar application of Zn was associated with decrease in cytokinin oxidase/dehydrogenase (TaCKX) and increase in kernel weight. In the present study, succinate dehydrogenase activity of the hyphae of indigenous arbuscular mycorrhizal fungi (IAMF) associated with plant roots was also assayed. Results disclose that succinate dehydrogenase activity of IAMF was significantly affected by Zn treatments during grain filling stages. Results showed that plant yield could be improved by foliar application of the exogenous hormone, 6-BAP, especially when applied in combination with Zn.